PENGARUH COACHING DAN MONITORING TERHADAP KINERJA KARYAWAN PT. SIMPATIK BORNEO UTAMA KAPUAS - Puspita Wulandari; Maryono; Taharuddin; Humaidi (Smart Business Journal (SBJ), 2026)
This study aims to examine the effect of coaching and monitoring on employee performance at PT. Simpatik Borneo Utama Kapuas. This study is motivated by a decline in employee performance, indicating issues in both the quantity and quality of work. This study uses a quantitative approach. The sample consists of 39 respondents. This study applies a non-probability sampling technique with a saturated sampling method. The researcher collects data using questionnaires and analyzes data using multiple linear regression. The results show that coaching (X1) has no significant effect on employee performance (Y). Monitoring (X2) has a positive and significant effect on employee performance (Y). Simultaneously, coaching (X1) and monitoring (X2) have a significant effect on employee performance (Y).